2021
DOI: 10.1093/infdis/jiab128
|View full text |Cite
|
Sign up to set email alerts
|

Prevention of Coronavirus Disease 2019 Among Older Adults Receiving Pneumococcal Conjugate Vaccine Suggests Interactions Between Streptococcus pneumoniae and Severe Acute Respiratory Syndrome Coronavirus 2 in the Respiratory Tract

Abstract: Introduction While secondary pneumococcal pneumonia occurs less commonly after COVID-19 than after other viral infections, it remains unclear whether other interactions occur between SARS-CoV-2 and Streptococcus pneumoniae. Methods We probed potential interactions between these pathogens among adults aged ≥65y by measuring associations of COVID-19 outcomes with pneumococcal vaccination (13-valent conjugate and 23-valent polys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
55
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 54 publications
(62 citation statements)
references
References 54 publications
(68 reference statements)
6
55
0
1
Order By: Relevance
“… 41 Recently, Streptococcus pneumoniae vaccines were also found to have a protective effect against COVID‐19 outcomes suggesting that pneumococci may interact with SARS‐CoV‐2 in the respiratory tract. 42 A double‐blind placebo‐randomized trial showed that the pneumococcal conjugate vaccine protects children against pneumococcal coinfections with seasonal coronaviruses. 43 Another suggestion was that pneumonia vaccination may prevent COVID‐19 exacerbation due to co‐infections or secondary bacterial infections.…”
Section: Discussionmentioning
confidence: 99%
“… 41 Recently, Streptococcus pneumoniae vaccines were also found to have a protective effect against COVID‐19 outcomes suggesting that pneumococci may interact with SARS‐CoV‐2 in the respiratory tract. 42 A double‐blind placebo‐randomized trial showed that the pneumococcal conjugate vaccine protects children against pneumococcal coinfections with seasonal coronaviruses. 43 Another suggestion was that pneumonia vaccination may prevent COVID‐19 exacerbation due to co‐infections or secondary bacterial infections.…”
Section: Discussionmentioning
confidence: 99%
“…National rates of vaccination with pneumococcal vaccines correlate inversely with case and death rates from COVID-19 [5,42] and pneumococcal vaccination has been demonstrated to lower the risk of coronavirus infections associated with pneumonias in children and adolescents [43]. Additionally, rates of pneumococcal vaccinations correlate inversely with the risk of COVID-19 in four separate cohort or case-controlled studies involving tens to hundreds of thousands of patients each [44][45][46][47]. More specifically, Sambul et al [48] found that antibody titers to pneumococcal vaccine antigens were correlated inversely with the risk of COVID-19: non-infected individuals averaged titers that were four times higher than those of COVID-19-infected individuals and (p = 0.002) and people with asymptomatic infections had significantly higher titers than people with severe cases (p = 0.01) [48].…”
Section: Non-sars-cov-2 Vaccinations and Covid-19 Riskmentioning
confidence: 97%
“…11 Whereas seasonal influenza vaccination was expected to reduce individuals' risk of study endpoints, 12 zoster vaccination was not expected to impact these disease outcomes. 13 We further recorded individuals' age at the beginning of each year, their history of healthcare utilization in the prior year (including numbers of outpatient visits, emergency department visits, and inpatient admissions), sex, race/ethnicity, tobacco smoking history, body mass index, history of comorbid conditions, and median household income within their residential census tract. Prior year comorbid conditions were determined from ICD-10-CM codes (Table S2).…”
Section: Exposuresmentioning
confidence: 99%